2020
DOI: 10.15446/dyna.v87n213.80446
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical modeling of surface water balance (SWB) under variable soil moisture conditions in the Pao river basin, Venezuela

Abstract: The aim of this paper is to develop a geostatistical model for the surface water balance (SWB) under variable soil moisture conditions of the Pao river basin, Venezuela. The novelty of the research consists in identifying a statistical model that will predict the spatial variability of hydro-meteorological data in the basin. A series of meteorological data from 25 stations for the period 2015-2017 were used in connection with the ordinary kriging technique. Infiltration values were analyzed considering three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The procedure is based on those carried out for studies made by the Center of Hydrological and Environmental Research of the University of Carabobo, Venezuela, in the basins of the San Diego and Pao Rivers, Carabobo state, Venezuela, [24][25][26][27]. It consists of two stages: 1) Compilation of information: a) Meteorology, b) Landsat satellite images and c) Digital elevation model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure is based on those carried out for studies made by the Center of Hydrological and Environmental Research of the University of Carabobo, Venezuela, in the basins of the San Diego and Pao Rivers, Carabobo state, Venezuela, [24][25][26][27]. It consists of two stages: 1) Compilation of information: a) Meteorology, b) Landsat satellite images and c) Digital elevation model.…”
Section: Methodsmentioning
confidence: 99%
“…In the Centre for Hydrological and Environmental Research of the University of Carabobo (Venezuela), (CIHAM-UC) research has been carried out using geostatistical and space-time prediction methods: a geostatistical model is established to predict the magnitude and location of the hydrometeorological variables involved in the water balance, [24].…”
Section: Introductionmentioning
confidence: 99%
“…A geostatistical model classified within the linear statistical models (probabilistic) known as Ordinary Kriging [7] was applied to predict the meteorological variables, precipitation, and evaporation. The experiences of using geostatistical models to predict the water balance have led to the establishment of mathematical functions that satisfactorily approximate the observations of the meteorological variables in the Pao and Urama river basins [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several scenarios are presented for a prospective time where the flood risk is gradually reduced as the predictable life parameter of hydraulic work is increased. By comparing to CIHAM-UC-FR model with that proposed by Farias et al (2020), it has been found that the former takes into account the effect of terrain elevation and slope on the effective precipitation estimate and its associated flood risk introducing an improvement with respect to the latter for mean to high terrain elevations and slopes.…”
Section: Introductionmentioning
confidence: 99%
“…In each case, the goal is the same: forecast the input design flow, run it through the system, and validate if the output is satisfactory. For instance, to make a rational use of the available water, it is necessary to know the amount required for irrigation and the time in which it must be supplied (e.g., using USDA‐FAS Palmer model [Mladenova et al., 2020]), what requires to make decisions supported in the spatio‐temporal forecast of the water balance over the area of interest (Farias et al., 2020).…”
Section: Introductionmentioning
confidence: 99%